2000
DOI: 10.1086/313843
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Immunodeficiency Virus–Associated Opportunistic Infections in the United States in the Era of Highly Active Antiretroviral Therapy

Abstract: The incidence of nearly all AIDS-defining opportunistic infections (OIs) decreased significantly in the United States during 1992-1998; decreases in the most common OIs (Pneumocystis carinii pneumonia ¿PCP, esophageal candidiasis, and disseminated Mycobacterium avium complex ¿MAC disease) were more pronounced in 1996-1998, during which time highly active antiretroviral therapy (HAART) was introduced into medical care. Those OIs that continue to occur do so at low CD4+ T lymphocyte counts, and persons whose CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
406
2
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(440 citation statements)
references
References 30 publications
18
406
2
14
Order By: Relevance
“…La disponibilidad del tratamiento antirretroviral de gran eficacia ha transformado el pronóstico del paciente infectado con el virus de inmunodeficiencia humana (HIV) en los últimos años (1,2), lo cual ha significado una reducción acentuada en la morbilidad y la mortalidad relacionadas con la infección (3). En el manejo a largo plazo del paciente con HIV, han surgido retos adicionales como la toxicidad de los medicamentos (4,5), el fracaso del tratamiento debido a un cumplimiento inadecuado (6,7), la resistencia a los medicamentos antirretrovirales (8) con el consecuente cambio en el esquema de tratamiento, y un incremento en la morbilidad y la mortalidad no asociadas al HIV (9,10).…”
unclassified
“…La disponibilidad del tratamiento antirretroviral de gran eficacia ha transformado el pronóstico del paciente infectado con el virus de inmunodeficiencia humana (HIV) en los últimos años (1,2), lo cual ha significado una reducción acentuada en la morbilidad y la mortalidad relacionadas con la infección (3). En el manejo a largo plazo del paciente con HIV, han surgido retos adicionales como la toxicidad de los medicamentos (4,5), el fracaso del tratamiento debido a un cumplimiento inadecuado (6,7), la resistencia a los medicamentos antirretrovirales (8) con el consecuente cambio en el esquema de tratamiento, y un incremento en la morbilidad y la mortalidad no asociadas al HIV (9,10).…”
unclassified
“…Those who develop PCP despite receipt of cART usually have a low CD4 count. In the ASD study the CD4 count among persons developing PCP while receiving cART was low (median=29 cells/µL), and was lower among those not taking cART (median=13 cells/µL) [11]. The prospective pan-European EuroSIDA study reported that the median CD4 count was 30 cells/µL among persons developing PCP while receiving cART, and was similar among those not receiving cART who got PCP [8].…”
Section: Before the Onset Of The Aids Epidemic Pcp Was Uncommon In Thmentioning
confidence: 97%
“…The advent of cART resulted in further declines in rates of PCP and other opportunistic infections [7][10] [11]. Several large, multicenter studies have tracked the incidence and epidemiologic features of PCP in the era of cART.…”
Section: Before the Onset Of The Aids Epidemic Pcp Was Uncommon In Thmentioning
confidence: 99%
“…El uso de TAR ha producido una disminución significativa en la incidencia de la criptococosis [13][14][15] . Se han realizado estimaciones que en el año 2006 se podrían haber producido unos 957.000 casos de meningitis criptocóccica en el mundo y que 624.725 personas podrían haber fallecido por esta causa 16 .…”
Section: Introductionunclassified